Effects of Cassava Substitute for Maize Based Diets on Performance Characteristics and Egg Quality of Laying Hens - Kyawt, Yin Yin; Toyama, Hidemi; Htwe, Win Mi; Thaikua, Sarayut; Imura, Yoshimi; Kawamoto , Yasuhiro (International Journal of Poultry Science, 2014)
The effects of feeding diets containing cassava meal (tuber and leaf) were investigated on feed intake, feed conversion ratio, weight gain, egg performance and egg quality of layer during 5 weeks of feeding experiment. Thirty-six white leghorn layer were allocated into 4 groups of nine hens each. Diet I, contained no cassava meal but maize 57% of the diet and served as the control. In diet II, III and IV, the proportion of maize was substituted with the cassava meal at the levels of 30% (30% tuber+0% leaf), 40% (30% tuber+10% leaf) and 50% (30% tuber+20% leaf), respectively. Egg laying rate tended to decrease with the IV, although there was no significant different between them. Haugh unit value in the hens fed diet III were significantly higher (p<0.05) than those fed other diets. Hens fed cassava meal diets had higher yolk color score than the control fed with maize based diet. The results demonstrated that, up to 40% of maize could be replaced with cassava meal for improving laying performance and egg quality. Moreover, supplementation with cassava leaf to tuber was efficient in lowering yolk cholesterol contents.